Tumor Cell Distinguishable Nanomedicine Integrating Chemotherapeutic Sensitization and Protection - Liu, Sen; Shen, Can; Qian, Cheng; Wang, Jianquan; Yang, Zhongmei; Wei, Yanchun; Quan, Li; Pan, Changjiang; Hu, Yong; Ye, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Theoretically, given at a high enough drug dosage, cancer cells could be eliminated. However, the dosages that can be administrated are limited by the therapeutic efficacy and side effects of the given drug. Herein, a nanomedicine integrating chemotherapeutic sensitization and protection was developed to relieve the limitation of administration dosage and to improve the efficacy of chemotherapy. The nanomedicine was endowed with the function of synergistically controlled release of CO and drugs under near-infrared (NIR) light irradiation. CO photo-induced release system (COPIRS) was synthesized by constructing an electron excitation–electron transfer group–electron-induced CO release structure and was used as the hydrophobic part, and then hydrophilic polymer (polyethylene glycol; PEG) was introduced by a thermal-responsive groups (DA group), forming a near-infrared-induced burst-release nanocarrier. In vitro and in vivo experiments showed that the nanomedicine can distinguish between tumor and normal cells and regulates the resistance of these different cells through the controlled release of carbonic oxide (CO), simultaneously enhancing the efficacy of chemotherapy drugs on tumor cells and chemotherapeutic protection on normal cells. This strategy could solve the current limitations on dosages due to toxicity and provide a solution for tumor cure by chemotherapy.